Biased Teachers and Gender Gap in Learning Outcomes: Evidence from India - Sonali Rakshit; Soham Sahoo (Global Labor Organization (GLO), 2020)
This paper investigates the effect of stereotypical beliefs of teachers on learning outcomes of secondary school students in India. We measure teacher's bias through an index capturing teacher's subjective beliefs about the role of gender and other characteristics in academic performance. We tackle the potential endogeneity of teacher's subjective beliefs by controlling for teacher fixed effects in a value-added model that includes lagged test score of students. We find that a standard deviation increase in biased attitude of the math teacher widens the female disadvantage in math performance by 0.07 standard deviation over an academic year. This negative effect of biased teachers is significant only for male teachers. The effect is especially strong among the medium-performing students and in classes where the majority of students are boys. Moreover, among the medium-performing students, having a female teacher significantly reduces the gender gap in math performance. As a plausible mechanism, we show that biased teachers negatively affect girls' attitude towards math as compared to boys. Unlike math outcome, we do not find any significant effect when we analyze the effect of biased English teachers on English scores of the same students.
Keywords: I24; J16; J24; 330; Learning outcomes; Value-added model; Gender; Teachers; Stereotypes; India